Women who write from the past and the present to the future - Smith, Lucinda (Englewood Cliffs, N.J. J. Messner, 1989)
Discusses the nature and significance of authorship and uses interviews and biographical profiles to analyze the contributions of notable women writers.
Keywords: Women and literature -- United States; American literature -- Women authors -- History and criticism; Authors, American; Authors, English; Authorship; Authorship; English literature -- Women authors -- History and criticism; Women and literature -- Great Britain; Women authors -- Interviews; Women authors, American; Women authors, English